EP-546 Management of breast cancer in different age groups during pandemic single institute review. (9th August 2022) - Muhibullah, Nazli; Ng, James; Cuffolo, Giulio; Whisker, Lisa
Abstract: Introduction: Covid 19 has huge impact on healthcare in general and challenges in cancer services in particular. In breast cancer prioritization strategies for management have been introduced at start of pandemic by different medical associations. Aim: We aim to see impact of prioritization strategy in treatment of premenopausal and postmenopausal breast cancer patient. This is further stratified as under 50, 50 to 70 and over 70. Methods: A prospectively collected database from March 2020 to March 2021 analysed. This include patient demographic, tumour characteristics, Neoadjuvanct endocrine NAET), Neoadjuvanct chemotherapy (NACT), primary endocrine (PE), type of surgery: breast conservation surgery (BCS) with or without oncoplastic procedure, Mastectomy with or without reconstruction and utilization of private sectors. Results: Total 454 patients reviewed. Mean age 61 yrs (26–97yrs). Total patient less than 50 years were 116. BCS 66 (57%), Simple mastectomy 26 (22%), Mastectomy with reconstruction 24 (20%).In this group 45 patients were offered NACT and 6 patients had NAET. Total patients older than 50 years were 236. BCS 191 (80%), Simple mastectomy 38 (16%) and Mastectomy with reconstruction 7(3%) patients. In this group 69 patients had NACT and 13 had NAET. Patients over 70 years were 102. BCS 57(56%), Simple mastectomy 25(24%), 1 (1%) had mastectomy and reconstruction. 8 patients had NACT, 13 had NAET and 30 had primary endocrine. Conclusion: Due to swift guidelines in pandemic times breast cancer services were largely intact and provide standard care.